OBSTACLE COURSE EXERCISE DAPAT MENINGKATAN KESEIMBANGAN DINAMIS ANAK AUTISME - Febriani, Yelva; Adenikheir, Annisa; Syah, Irhas (Prodi Fisioterapi UFDK, 2023)
ABSTRACKChildren with autism not only have communication and social difficulties but also show poor balance and motor control abilities that can affect daily activities, besides that, postural instability is closely related to balance disorders. Effective balance and motor control will depend on somatosensory, visual and vestibular input. The type of research used is quasi-experimental with a one group pre-post test approach. Sampling by purposive sampling with a sample of 10 respondents. Obstacle course training was given for 12 interventions for 2 weeks. The dynamic balance results before and after giving Obstacle course Exercise were 16.94 seconds and 13.64 seconds. The effect test results obtained p = 0.005 <α (0.05). From the results of the study it can be concluded that the Obstacle course Exercise has an effect on increasing the dynamic balance of children with autism.Keywords: Obstacle course Exercise, dynamic balance, autism